Revision of the genus Prionotropis Fieber, 1853 (Orthoptera: Pamphagidae: Thrinchinae) - Massa, Bruno; Ünal, Mustafa; Verde, Gabriella Lo (Zootaxa, 2015)
The genus Prionotropis Fieber, 1853 is revised. It is distributed in scattered areas of the Mediterranean region from Turkey in the East to Spain in the West. Overall, seven species are listed, namely P. maculinervis (Stål, 1878) (Turkey; P. urfensis Ramme, 1933 is here considered its synonym), P. willemsorum n. sp. (Greece, Epirus; previously considered P. appula), P. appula (O.G. Costa, 1836) (South Italy), P. hystrix (Germar, 1817) (Bosnia and Herzegovina, Slovenia, Croatia, North-East Italy; P. hystrix sontiaca is here synonymized), P. rhodanica Uvarov, 1923 resurrected status (France, Crau, Rhone delta; here considered a valid species), P. azami Uvarov, 1923 n. status (France, Var region; here considered a valid species), and P. flexuosa (Serville, 1838) (Spain; the ssp. pereezi Bolívar, 1921 and sulphurans Bolívar, 1921 are here considered its synonyms). A key to species is presented.